1996
DOI: 10.1002/(sici)1097-0215(19960529)66:5<627::aid-ijc8>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in fathers and brothers of testicular cancer patients in Denmark. A population‐based study

Abstract: There are several reports of familial testicular cancer in the literature but few systematic attempts have been made to estimate the risk of testicular cancer in first-degree relatives of patients with this neoplasm, and the risk remains to be fully assessed in population-based studies. By means of data from the Danish Cancer Registry, we identified all testicular cancer patients (index cases) born and diagnosed during 1950-I993 in Denmark. Their fathers were identified from national registries, as were the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 12 publications
(14 reference statements)
2
37
1
1
Order By: Relevance
“…Familial studies have shown strong evidence for inherited susceptibility for testicular cancer. Sons whose fathers have testicular cancer have fourtimes the risk of testicular cancer, and brothers of patients with testicular cancer have eight-times the risk of having testicular cancer [25][26][27]. An excess familial risk for testicular cancer was also shown in a large twin cohort study in Nordic countries [28].…”
Section: Discussionmentioning
confidence: 87%
“…Familial studies have shown strong evidence for inherited susceptibility for testicular cancer. Sons whose fathers have testicular cancer have fourtimes the risk of testicular cancer, and brothers of patients with testicular cancer have eight-times the risk of having testicular cancer [25][26][27]. An excess familial risk for testicular cancer was also shown in a large twin cohort study in Nordic countries [28].…”
Section: Discussionmentioning
confidence: 87%
“…Taken together with the most recent studies, it seems fair to conclude that exposure to exogenous oestrogens in early pregnancy is associated with only a modest increase in risk of male offspring developing testis cancer. However, two new studies show that twins of brothers who have had testicular cancer have a 12-to 37-fold increased risk of testicular cancer themselves (Westergaard et al, 1996;Swerdlow et al, 1997), raising the possibility that the increased risk stems in part from increased exposure to endogenous (maternal) oestrogens, especially as the risk is 50-100% higher in dyzgotic, than in monozygotic, twins (Braun et al, 1995;Swerdlow et al, 1997) in which oestrogen levels are well established to be higher. Another study has shown that twin and non-twin brothers of men who develop testicular cancer are at 9-13-fold greater risk of developing testicular cancer themselves (Sonneveld et al, 1999).…”
Section: Testicular Cancermentioning
confidence: 99%
“…Other relevant findings from these studies help this debate a little. For example, one of the studies cited also investigated risk in the fathers of men who developed testicular cancer and showed that risk was increased only 2-fold (Westergaard et al, 1996;Sonneveld et al, 1999). Interestingly, the studies by Braun et al (1995) and Swerdlow et al (1997) showed that twin girls were also at higher risk of breast cancer.…”
Section: Testicular Cancermentioning
confidence: 99%
“…In several other familial cancer syndromes, cancers other than the primary malignancy of interest have been found to occur excessively in at-risk family members, such as hereditary breast-ovarian cancer, multiple endocrine neoplasia types I and II, and hereditary nonpolypo-sis colon cancer, among others. Several prior studies have analyzed cancer risk in relatives of nonfamilial (sporadic) TGCT patients [12,14,[31][32][33][34][35][36][37][38][39][40][41][42][43][44], but an excess risk of testicular cancer has been the only consistent finding in these reports. Results related to cancers other than TGCT have been inconsistent and contradictory.…”
Section: Introductionmentioning
confidence: 99%